2015
DOI: 10.33549/physiolres.932851
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Training Attenuates Sympathetic Activation and Oxidative Stress in Diet-Induced Obesity

Li G1,
et al.

Abstract: It is known that excessive sympathetic activity and oxidative stress are enhanced in obesity. This study aimed to clarify whether exercise training (ET) attenuates sympathetic activation and oxidative stress in obesity. The obesity was induced by high-fat diet (HFD) for 12 weeks. Male Sprague-Dawley rats were assigned to four groups: regular diet (RD) plus sedentary (RD-S), RD plus ET (RD-ET), HFD plus sedentary (HFD-S), and HFD plus ET (HFD-ET). The rats in RD-ET and HFD-ET groups were trained on a motorized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 52 publications
(43 reference statements)
2
12
0
5
Order By: Relevance
“…This idea is supported by the fact that we found increased antioxidant enzyme activity in the plasma and tissues of the VR rats. These results are in agreement with research which shows that exercise reduces oxidative stress [ 53 ].…”
Section: Discussionsupporting
confidence: 93%
“…This idea is supported by the fact that we found increased antioxidant enzyme activity in the plasma and tissues of the VR rats. These results are in agreement with research which shows that exercise reduces oxidative stress [ 53 ].…”
Section: Discussionsupporting
confidence: 93%
“…These results corroborates a well-known positive effect of physical exercise on oxidative stress biomarkers. 28 With regard to the antioxidant enzymes, results showed that HFD did not alter SOD activity in the soleus muscle, but reduced this enzyme's activity in the plantaris muscle. The MICT protocol enhanced SOD activity in the soleus muscle and both protocols reversed the decrease in SOD activity caused by HFD in the plantaris muscle of rats.…”
Section: Discussionmentioning
confidence: 93%
“…This receptor has been implicated in the development of insulin resistance (Shi et al 2006) and reductions in TLR4 protein may be a mechanism for resistance exercise-induced increases in insulin sensitivity (Croymans et al 2013). Relatively few studies have attempted to capture the acute or prolonged effect of exercise on muscle TLR4 protein (Lambert et al 2008;Ghosh et al 2015;Li et al 2015). Twelve weeks of combined endurance and resistance exercise training has been shown to be more effective than diet-induced weight loss at reducing total muscle TLR4 protein content in older adults with obesity (Lambert et al 2008).…”
Section: Discussionmentioning
confidence: 99%